Nyalam Adat ba' Alam: Swidden Cultivation and Political-Ecological Dynamics among the Dayak Krio, West Kalimantan, Indonesia - Uswatun Khasanah Enggar Saptaningrum; Rafi Rendian Sulaksono (Endogami: Jurnal Ilmiah Kajian Antropologi, 2025)
This study examines the sustainability of swidden cultivation among the Dayak Krio community living around the Krio River in Hulu Sungai Subdistrict, Ketapang Regency, West Kalimantan Province, within a political ecology framework. The problem formulation centers on how practices that are often stigmatized by the state and companies as "ancient" or "environmentally destructive" continue to function as subsistence strategies and political negotiations for access to forest land. A qualitative ethnographic approach guided the collection of data through literature studies, participant observation, semi-structured interviews, focus group discussions, and documentation during fieldwork with Gaia Indonesia in the Forest Village Social Study project in West Kalimantan in August 2025. The findings reveal that swidden cultivation is a ritualized socio-ecological system that encodes local knowledge and spiritual relationships regarding the human-nature relationship inherited from thousands of years ago, not merely a traditional farming technique. Furthermore, the stigmatization of swidden cultivation by state law and corporate narratives serves to legitimize external control over forest land, intensifying contestation over forest access. In conclusion, Dayak Krio swidden cultivation embodies resilience, representing a negotiated strategy to maintain survival, cultural identity, and ecological sustainability amid expanding agribusiness and limiting policies.